(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
For fertilization to happen, the foremost is sperm and an egg cell. In detailed study on fertilization, scientist had shown the mystery behind fertilization, that most important is the surface protein receptors, which is found on the surface of an egg cell, named Izumo and a similar complimentary receptor found on the surface of sperm cell, named Juno. Discovery of Izumo and Juno has created a breakthrough in the field of infertility research which will surely help infertile patients with a new ray of hope.